Influência da codigestão anaeróbia de biomassa mixotrófica no desaguamento do lodo de descarte de um UASB tratando esgoto sanitário - Louzada, Larissa Miranda (2018)
The aim of this research was to evaluate the influence of the codigestion of mixotrofic biomass on the ability to dewatering sludge from a UASB treating sewage. The anaerobic codigestion of sewage and a second carbonaceous source have been studied aiming to fortify the advantages of combining treatment systems. However, despite the relevance of the sludge processing stages in relation to the economic and environmental issues of a WWTP, studies about the influence of this technique on the dewatering of the sludge produced are scarce. In this work, a pilot scale UASB reactor was operated and monitored over two stages. In Step 1, data on sludge production were observed, natural dewatering tests were carried out in an apparatus and the physical, chemical and biological characterization of the sludge samples was performed by UASB treating sanitary sewage at a flow rate of 0.12 L/s organic load rate of 4.3 kgCOD/d. In Step 2 the same methodology was applied on the reactor treating sewage and mixotrofic biomass obtained by the physical-chemical pathway without previous hydrolysis processing. At this stage the flow rate was 0.13 L/s and the organic load rate was 3.7 kgCOD/d. Sludge production was 0.4 kgTS/d and 0.2 kgVS/d in Phase 1 and 0.3 kgTS/d and 0.2 kgVS/d in Phase 2. The sludge age was reduced from 108 days to 98 days and the amount of free water in the samples reduced from 83% to 72%. The best results of the dewatering test indicate 80% reduction of initial volume for Step 1 and 56% of the same parameter for Step 2. The data suggest that the codigestion performed according to the methodology of this research has resulted in damage to the sludge dewatering by non-mechanized methods and pointed out an abnormal behavior of the sludge blanket due to the low density of the mixotrofic biomass, causing it to suffer a drag due to the ascensional velocity. No changes were observed in the physical-chemical characterization of the samples, however, there was an increase in the amount of EPS in the reactor during Step 2. The AME data showed that there was no inhibitory effect caused by the reactor feed with algae sludge.